Coating metal sulfide layer and its manufacturing method

A coated metal sulfide layer with a specific sulfur-to-metal ratio and a metal oxide coating addresses the capacity and cycle life issues in lithium-ion batteries by enhancing cycle stability and capacity retention.

JP7607958B2Active Publication Date: 2025-01-06NATIONAL INSTITUTE OF ADVANCED INDUSTRIAL SCIENCE & TECHNOLOGY
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2022580662
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-02-10
Filing Date
2022-02-09
Publication Date
2025-01-06
Estimated Expiration
2042-02-09

AI Technical Summary

Technical Problem

Current lithium-ion secondary batteries have insufficient positive electrode capacity and poor charge-discharge cycle characteristics due to the elution of sulfur-based active materials into organic electrolytes, which degrades their performance over time.

Method used

A coated metal sulfide layer with a specific composition ratio of sulfur to metal (S/M 1 = 2.1 to 10 molar ratio) is coated with a metal oxide layer, enhancing the charge-discharge cycle characteristics without reducing initial capacity.

Benefits of technology

The coated metal sulfide layer improves charge-discharge cycle characteristics while maintaining initial capacity, making it suitable for use in lithium-ion secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007607958000003
    Figure 0007607958000003
  • Figure 0007607958000004
    Figure 0007607958000004
  • Figure 0007607958000005
    Figure 0007607958000005
Patent Text Reader

Abstract

In the present invention, part or all of a metal sulfide layer including a metal sulfide is coated with a coating layer including a metal oxide. The metal sulfide is such that the compositional ratio (S / M1) of sulfur and metal is 2.1-10 by molar ratio. The coated metal sulfide layer can improve the charge / discharge cycle characteristics without lowering the initial capacity of a lithium-ion secondary battery.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a coating metal sulfide layer and a method for producing the same. [Background technology]

[0002] In recent years, the increasing performance of portable electronic devices, hybrid vehicles, etc. has led to a demand for increasingly higher capacity lithium-ion secondary batteries used in them. However, current lithium-ion secondary batteries have insufficient capacity in the positive electrode compared to the negative electrode, and even lithium nickel oxide-based materials, which are said to have relatively high capacity, have a capacity of only about 190 to 220 mAh / g.

[0003] On the other hand, sulfur has a high theoretical capacity of approximately 1670 mAh / g, and is expected to be used as a positive electrode active material, but it is generally known that the capacity of sulfur-based positive electrode active materials decreases with repeated charge-discharge cycles. This is because sulfur dissolves into the organic electrolyte as lithium polysulfide during charging and discharging, so technology to suppress its dissolution into the organic electrolyte is essential.

[0004] Metal sulfides have electronic conductivity and little elution into organic electrolytes, but this is not sufficient. For example, vanadium sulfide is used as a metal sulfide. When crystalline vanadium sulfide (III) (V2S3) sold as a reagent is used as a positive electrode active material, the reaction with the organic electrolyte cannot be suppressed, and the measured capacity is only about 23 mAh / g charge capacity and 52 mAh / g discharge capacity. In contrast, the present inventors have reported that low-crystalline vanadium sulfide having a specific composition exhibits high capacity and excellent charge / discharge cycle characteristics when used as an electrode active material for lithium-ion secondary batteries (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2018 / 181698 Summary of the Invention [Problem to be solved by the invention]

[0006] As described above, the inventors have developed a material that exhibits high capacity when used as an electrode active material for lithium ion secondary batteries and also has excellent charge-discharge cycle characteristics. However, there is a continuing demand for higher performance lithium ion secondary batteries, and further improvements in the charge-discharge cycle characteristics are required.

[0007] The present invention has been made in consideration of the current state of the prior art described above, and a main object of the present invention is to provide a material that improves charge-discharge cycle characteristics without reducing the initial capacity. [Means for solving the problem]

[0008] The present inventors have conducted extensive research to achieve the above object. As a result, the composition ratio of sulfur to metal (S / M 1 It has been found that a coated metal sulfide layer in which a metal sulfide layer (not metal sulfide particles) containing a metal sulfide having a molar ratio of 2.1 to 10 is entirely or partially coated with a coating layer containing a metal oxide can solve the above problems and improve charge / discharge cycle characteristics without decreasing the initial capacity. The present invention has been completed as a result of further research based on these findings. That is, the present invention includes the following configurations.

[0009] Item 1. All or a part of a metal sulfide layer containing a metal sulfide is coated with a coating layer containing a metal oxide, and The metal sulfide has a sulfur to metal composition ratio (S / M 1 ) is 2.1 to 10 in a molar ratio.

[0010] Item 2. The coated metal sulfide layer according to Item 1, wherein the coating layer has a coverage of 50 to 100%.

[0011] Item 3. The coated metal sulfide layer according to Item 1 or 2, wherein the metal sulfide has an average particle size of 1.0 to 20.0 μm.

[0012] Item 4. The coated metal sulfide layer according to any one of Items 1 to 3, wherein the metal sulfide layer has a thickness of 0.010 to 1.00 mm.

[0013] Item 5. The coated metal sulfide layer according to any one of Items 1 to 4, wherein the metal oxide is an oxide of titanium and / or aluminum.

[0014] Item 6. The coated metal sulfide layer according to any one of Items 1 to 5, wherein the metal sulfide is vanadium sulfide.

[0015] Item 7. A method for producing a coated metal sulfide layer according to any one of items 1 to 6, (1A) applying a solution of a metal alkoxide to the surface of the metal sulfide layer; or (1B) A step of coating the surface of the metal sulfide layer with the metal oxide by a sputtering method. A manufacturing method comprising:

[0016] Item 8. The method according to Item 7, wherein the solvent in the solution of the metal alkoxide is an alcohol having 3 to 6 carbon atoms.

[0017] Item 9. After the step (1A), (2A) Exposure to the atmosphere The manufacturing method according to item 7 or 8, comprising:

[0018] Item 10. After the step (1A), (1B) or (2A), (3) Heat treatment process The method for producing the same according to any one of items 7 to 9, comprising:

[0019] Item 11. A positive electrode for a lithium ion secondary battery, comprising the coating metal sulfide layer according to any one of items 1 to 6.

[0020] Item 12. A lithium ion secondary battery comprising the positive electrode for lithium ion secondary batteries according to item 11. Effect of the Invention

[0021] According to the present invention, it is possible to improve the charge-discharge cycle characteristics without decreasing the initial capacity. [Brief description of the drawings]

[0022] [Figure 1] The results of cross-sectional scanning electron microscope observation (cross-sectional SEM) and EDX observation of the coated vanadium sulfide layer (positive electrode) obtained in Example 3 and the vanadium sulfide layer obtained in Synthesis Example 2 (vanadium sulfide layer (positive electrode) of Comparative Example 1) are shown. The left image is a secondary electron image by cross-sectional SEM, the middle image is an EDX image of titanium, and the right image is an EDX image of oxygen. [Diagram 2] 4 shows the element concentration distribution of the coated vanadium sulfide layer (positive electrode) obtained in Example 3. [Diagram 3] 1 shows a comparison of the discharge capacities of the vanadium sulfide coated layers and the vanadium sulfide layers obtained in Example 3 and Comparative Example 1 in accordance with charge-discharge cycles. [Figure 4] The results of cross-sectional scanning electron microscope observation (cross-sectional SEM) and EDX observation of the coated vanadium sulfide layer (positive electrode) obtained in Example 17 and the vanadium sulfide layer obtained in Synthesis Example 2 (vanadium sulfide layer (positive electrode) of Comparative Example 1) are shown. The left image is a secondary electron image by cross-sectional SEM, the middle image is an EDX image of aluminum, and the right image is an EDX image of oxygen. [Diagram 5] 1 shows the element concentration distribution of the coated vanadium sulfide layer (positive electrode) obtained in Example 17. [Figure 6] 1 shows a comparison of the discharge capacities of the vanadium sulfide coated layers and the vanadium sulfide layers obtained in Example 17 and Comparative Example 1 in accordance with charge-discharge cycles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] In this specification, "containing" is a concept that encompasses all of "comprise," "consist essentially of," and "consist only of." In addition, in this specification, when a numerical range is shown as "A to B," it means A or more and B or less.

[0024] 1. Metal sulfide coating layer The coated metal sulfide layer of the present invention is a metal sulfide layer containing a metal sulfide, all or a part of which is coated with a coating layer containing a metal oxide, and The metal sulfide has a sulfur to metal composition ratio (S / M 1 ) is in a molar ratio of 2.1 to 10.

[0025] (1-1) Metal sulfide In the present invention, the metal sulfide is not particularly limited as long as it is a metal sulfide known as a positive electrode active material for lithium ion secondary batteries. Specifically, vanadium sulfide (WO 2018 / 181698), lithium titanium sulfide, lithium niobium sulfide and lithium titanium niobium sulfide (WO 2014 / 148432), (lithium) niobium sulfide and (lithium) titanium niobium sulfide (WO 2015 / 049986), lithium tin sulfide (JP 2018-111616 A and JP 2018-172244 A), etc. can be mentioned. Among the above metal sulfides, those containing lithium (for example, lithium titanium sulfide, etc.) need to be handled under an inert atmosphere such as an argon gas atmosphere, so metal sulfides that do not contain lithium are preferred. The descriptions in International Publication No. 2018 / 181698, International Publication No. 2014 / 148432, International Publication No. 2015 / 049986, JP 2018-111616 A and JP 2018-172244 A are incorporated by reference. These metal sulfides can be used alone or in combination of two or more. Among these, vanadium sulfide has a higher discharge capacity than other metal polysulfides (niobium sulfide, titanium niobium sulfide, etc.), and vanadium sulfide is preferred from the viewpoint of constructing a high energy density battery aimed at practical use.

[0026] Such metal sulfides may be either crystalline or low-crystalline (or amorphous) materials. Among them, low-crystalline (or amorphous) materials are preferred from the viewpoint of charge / discharge capacity.

[0027] In the present invention, the average particle size of the metal sulfide is preferably 1.0 to 20.0 μm, more preferably 1.5 to 8.0 μm, and more preferably 2.0 to 5.0 μm, from the viewpoint of facilitating the maintenance of charge / discharge capacity and facilitating the improvement of charge / discharge cycle characteristics. The average particle size of the metal sulfide is calculated by electron microscope (SEM) observation, assuming a field of view of 13 μm×9 μm and an average number of 10 or more particles.

[0028] In the present invention, the metal sulfide has a composition ratio of sulfur to metal (S / M 1 The molar ratio of sulfur to metal (S / M) is 2.1 to 10. 1 If the molar ratio of sulfur to metal (S / M) is less than 2.1, the substance is not originally one that dissolves excessively into the organic electrolyte, and therefore the effect of improving the charge-discharge cycle characteristics by coating with a coating layer containing a metal oxide is not observed. 1 It is difficult to synthesize a metal sulfide with a molar ratio of 10 or more. From the viewpoint of easily suppressing a reaction with an organic electrolyte if the metal sulfide comes into contact with the organic electrolyte, a low-crystalline material is preferable.

[0029] More specifically, the metal sulfide has the general formula (1): M 1 Sx (1) [In the formula, M 1 indicates a metal. x is 2.1 to 10. It is preferable that the composition is represented by the formula: 1 When multiple metals are included, the composition ratio of sulfur to the total amount of metals (S / M 1 ) is preferably in a molar ratio of 2.1 to 10.

[0030] Thus, in the present invention, the metal sulfide is a metal (M 1 ) is high. Therefore, in the present invention, by using a metal sulfide, it is possible to have a high charge / discharge capacity. In the present invention, the higher the sulfur content (the larger x), the higher the charge / discharge capacity, and the lower the sulfur content (the smaller x), the less elemental sulfur is contained, and the higher the charge / discharge cycle characteristics. In the present invention, even if a sulfide with poor charge / discharge cycle characteristics is used, the charge / discharge cycle characteristics can be improved by forming a coating layer containing a metal oxide described later on the metal sulfide layer, so that it is particularly useful to apply a polysulfide that is likely to have a high charge / discharge capacity but is likely to have a deteriorated charge / discharge cycle characteristics. For this reason, x is 2.1 to 10, preferably 3 to 8.

[0031] Hereinafter, the preferred sulfide, vanadium sulfide, will be described as an example.

[0032] In the present invention, the vanadium sulfide preferably has a crystal structure similar to that of crystalline vanadium(IV) tetrasulfide (VS4) (hereinafter sometimes referred to as "VS4 type crystal structure").

[0033] More specifically, vanadium sulfide preferably has peaks at 15.4°, 35.3°, and 45.0° with a tolerance of ±1.0° within the diffraction angle 2θ range of 10° to 80° in an X-ray diffraction diagram using CuKα radiation. In other words, it preferably has peaks in the ranges of 14.4° to 16.4°, 34.3° to 36.3°, and 44.0° to 46.0°.

[0034] In the present invention, the X-ray diffraction pattern is obtained by powder X-ray diffraction measurement (θ-2θ method) under the following measurement conditions: Measuring device: D8ADVANCE (BrukerAXS) X-ray source: CuKα40kV / 40mA Measurement conditions: 2θ=10°~80°, 0.1° step, scanning speed 0.02° / sec Measured at.

[0035] In the present invention, vanadium sulfide preferably has a peak at the 2θ position described above, but also preferably has a peak at at least one (particularly all) of 54.0° and 56.0° within the diffraction angle 2θ range of 10° to 80°, with an allowable range of ±1.0°.

[0036] In the present invention, vanadium sulfide is a sulfide having a high ratio of sulfur in the average composition, but sulfur is hardly present as elemental sulfur as described later, and is preferably bonded with vanadium to form a low-crystalline sulfide. In this way, in the present invention, vanadium sulfide has a low crystallinity, and by lowering the crystallinity, it is possible to have more sites where lithium ions can be inserted and removed, and also to easily have gaps that can be three-dimensionally conductive paths for lithium. In addition, it has many advantages, such as being easily subjected to three-dimensional volume changes during charging and discharging. For this reason, it is possible to further improve the charge and discharge capacity. In addition, it is preferable that vanadium sulfide (such as V2S3) used as a raw material is hardly present. In this specification, the average composition of the sulfide refers to the element ratio of each element that constitutes the entire sulfide.

[0037] Hereinafter, the "low crystallinity" in the present invention will be described. In the present invention, in the vanadium sulfide, the full width at half maximum of the peaks at 2θ=15.4°, 35.3°, and 45.0° is preferably 0.8 to 2.0° (particularly 0.9 to 1.6°). In addition, in the crystalline vanadium (IV) sulfide (VS4), the full width at half maximum of the peaks at 2θ=15.4°, 35.3°, and 45.0° is preferably 0.2 to 0.6°. Thus, in the present invention, the vanadium sulfide preferably has a larger full width at half maximum of the peaks at 2θ=15.4°, 35.3°, and 45.0° than the crystalline vanadium (IV) sulfide (VS4). Thus, in the present invention, the low crystallinity makes it easier to increase the number of sites where Li can exist stably, and therefore, when the metal sulfide of the present invention is used as a positive electrode active material, the charge / discharge capacity and charge / discharge cycle characteristics are easily improved.

[0038] In addition, when a material containing a large amount of elemental sulfur is used as a positive electrode active material, the range of solvent selection is narrow because carbonate-based solvents react with elemental sulfur, and ether-based solvents dissolve a large amount of sulfur components, causing performance deterioration. In contrast, in the present invention, for example, when mechanical milling is performed for a sufficient time, the above-mentioned vanadium sulfide contains almost no elemental sulfur, etc., so when used as a positive electrode active material, these problems do not occur even when a carbonate-based solvent or an ether-based solvent is used, and the selectivity of the solvent for the electrolyte is easily improved.

[0039] More specifically, the strongest peak of sulfur (S8) is present at 2θ=23.0° within a tolerance range of ±1.0°. For this reason, in the X-ray diffraction pattern by CuKα radiation, it is preferable that there is no peak having a maximum at 2θ=23.0°, which is a peak characteristic of elemental sulfur, within a tolerance range of ±1.0°, or the area of ​​the peak having a maximum at 2θ=23.0° is 20% or less (0 to 20%, particularly 0.1 to 19%) of the area of ​​the peak having a maximum at 2θ=35.3°. As a result, in the present invention, the vanadium sulfide can be a material that contains almost no elemental sulfur, which reduces the concern of causing the reaction with the electrolyte as described above, and can further improve the charge / discharge capacity and charge / discharge cycle characteristics.

[0040] In the present invention, the vanadium sulfide preferably does not have peaks at 2θ=25.8° and 27.8°, which are peaks characteristic of elemental sulfur, or the area of ​​the peak having a maximum at said positions is 10% or less (0 to 10%, particularly 0.1 to 8%) of the area of ​​the peak having a maximum at 2θ=35.3°, within a tolerance range of ±1.0°. This allows the vanadium sulfide to be a material that contains almost no elemental sulfur, which reduces the concern of causing the above-mentioned reaction with the electrolyte, and further improves the charge / discharge capacity and charge / discharge cycle characteristics.

[0041] Vanadium sulfides that satisfy these conditions have a strong peak at g(r)=2.4 Å within a tolerance of ±0.1 Å in X-ray / neutron atomic pair correlation function analysis (PDF analysis), but sulfides with better charge / discharge capacity and charge / discharge cycle characteristics preferably have a shoulder peak at g(r)=2.0 Å and also preferably have a peak at g(r)=3.3 Å. In other words, vanadium sulfides preferably have not only VS bonds but also SS bonds (disulfide bonds).

[0042] In the present invention, the above-mentioned vanadium sulfide can be obtained, for example, by a production method using vanadium sulfide and sulfur as raw materials or intermediates, the production method including a step of subjecting the raw materials or intermediates to a mechanical milling method.

[0043] Mechanical milling is a method of grinding and mixing raw materials while applying mechanical energy. According to this method, the raw materials are ground and mixed by applying mechanical impact and friction, so that vanadium sulfide and sulfur come into vigorous contact with each other and are finely divided, causing a reaction of the raw materials. In other words, mixing, grinding, and reaction occur simultaneously. Therefore, it is possible to make the raw materials react more reliably without heating them to high temperatures. By using mechanical milling, a metastable crystal structure that cannot be obtained by normal heat treatment can be obtained.

[0044] Specifically, the mechanical milling treatment can involve mixed pulverization using a mechanical pulverizing device such as a ball mill, a bead mill, a rod mill, a vibration mill, a disk mill, a hammer mill, or a jet mill.

[0045] These raw materials or intermediates can be all mixed together and subjected to mechanical milling, or some of the materials or intermediates can be subjected to mechanical milling first, and then the remaining materials can be added and subjected to mechanical milling.

[0046] In particular, when producing vanadium sulfide with a high sulfur content (the composition ratio (S / V) of sulfur to vanadium is 3.3 or more in molar ratio), crystalline vanadium sulfide may be obtained depending on the charged mass. Therefore, in order to easily obtain low-crystalline vanadium sulfide with excellent charge / discharge capacity and charge / discharge cycle characteristics, it is preferable to first subject vanadium sulfide and a part of sulfur to mechanical milling treatment to obtain a desired low-crystalline sulfide as an intermediate, and then subject the obtained low-crystalline sulfide and the remaining sulfur to mechanical milling treatment.

[0047] As a specific raw material, it is preferable to use crystalline vanadium(III) sulfide (V2S3) as vanadium sulfide. There is no particular limitation on the vanadium sulfide, and any commercially available vanadium sulfide can be used. In particular, it is preferable to use a high-purity one. In addition, since the vanadium sulfide is mixed and pulverized by mechanical milling, there is no limitation on the particle size of the vanadium sulfide used, and usually, commercially available powdered vanadium sulfide can be used.

[0048] As for sulfur, elemental sulfur (S8) can be used in an amount necessary to form a sulfide of the desired composition. There is no particular limitation on the sulfur used as a raw material, and any sulfur can be used. In particular, it is preferable to use sulfur of high purity. In addition, since the sulfur is mixed and pulverized by mechanical milling, there is no limitation on the particle size of the sulfur used, and commercially available powdered sulfur can usually be used.

[0049] Furthermore, as described above, when the mechanical milling process is performed in multiple steps (particularly in two steps), the intermediate product is a low-crystalline vanadium sulfide having a desired composition (low-crystalline VS 2.5 etc.) can also be used.

[0050] The mixing ratio of the raw materials can be the same as the element ratio of vanadium and sulfur in the target vanadium sulfide, since the ratio of the raw materials is almost the same as the ratio of each element in the product. For example, it is preferable to use 1.2 moles or more (particularly 1.2 to 17.0 moles, more preferably 3.0 to 13.0 moles) of sulfur per mole of vanadium sulfide.

[0051] The temperature at which the mechanical milling treatment is carried out is not particularly limited, but is preferably 300° C. or lower, more preferably −10 to 200° C., in order to make it difficult for sulfur to volatilize and to make it difficult for the previously reported crystal phase to be formed.

[0052] The time for the mechanical milling treatment is not particularly limited, and the mechanical milling treatment can be carried out for any time until the desired vanadium sulfide is precipitated.

[0053] The atmosphere in which the mechanical milling process is carried out is not particularly limited, but an inert gas atmosphere such as a nitrogen gas atmosphere or an argon gas atmosphere can be used.

[0054] For example, the mechanical milling treatment can be carried out with an energy amount of 0.1 to 100 kWh / kg of raw material mixture within a treatment time range of 0.1 to 100 hours (particularly 15 to 80 hours). Note that this mechanical milling treatment can also be carried out in multiple steps with breaks in between, if necessary.

[0055] When the mechanical milling process is repeated multiple times, the above conditions can be applied to each mechanical milling process.

[0056] By the above-mentioned mechanical milling treatment, the target vanadium sulfide can be obtained as a fine powder.

[0057] (1-2) Metal sulfide layer The metal sulfide layer is not particularly limited as long as it contains the above-mentioned metal sulfide. However, taking into consideration that the coated metal sulfide layer of the present invention is used as a positive electrode, it is preferable that the metal sulfide layer has the same structure as the positive electrode.

[0058] Specifically, a composition that can be used as a positive electrode mixture prepared by mixing the above-mentioned metal sulfide with a conductive assistant and a binder as necessary can be supported on a carrier that can be used as a positive electrode current collector, such as aluminum, nickel, titanium, gold, silver, copper, stainless steel, or carbon cloth.

[0059] Examples of the conductive assistant include carbon materials (graphite, coke, carbon black, activated carbon, etc.), conductive fibers (acicular carbon; carbon nanotubes; vapor-grown carbon; fibers produced by carbonizing pitch (a by-product of petroleum, coal, coal tar, etc.) at high temperatures; carbon fibers produced from acrylic fibers), corrosion-resistant metals (titanium, gold, etc.), carbides (SiC, WC, etc.), nitrides (Si3N4, BN, etc.), etc. These conductive assistants can be used alone or in combination of two or more.

[0060] The content of the conductive assistant is not particularly limited, but from the viewpoint of easily maintaining the charge / discharge capacity and easily improving the charge / discharge cycle characteristics, it is preferably 3 to 30 mass%, more preferably 5 to 15 mass%, based on the total amount of the metal sulfide layer being 100 mass%. When a plurality of conductive assistants are used, it is preferable to adjust the total content of the conductive assistants to be within the above range.

[0061] The binder is not particularly limited and may be a known material, such as styrene-butadiene rubber, carboxymethyl cellulose, polyvinylidene fluoride (PVDF), polyimide, etc. Also, a binder having a reactive group that crosslinks by heating, ultraviolet irradiation, etc. may be suitably used. Examples of the reactive group include a vinylene group, a hydroxyl group, an epoxy group, an allyl group, a carbonyl group, and a reactive group in which a part of the carbon atom of the reactive group is substituted with a different element. These binders may be used alone or in combination of two or more kinds.

[0062] The content of the binder is not particularly limited, but from the viewpoint of easily maintaining the charge / discharge capacity and easily improving the charge / discharge cycle characteristics, the content is preferably 0.5 to 30 mass%, more preferably 1 to 25 mass%, based on the total amount of the metal sulfide layer being 100 mass%. When a plurality of binders are used, it is preferable to adjust the total content of the binders to be within the above range.

[0063] The shape of the carrier that can be used as the positive electrode current collector is not particularly limited, and examples thereof include metal foil (thickness 10 to 100 μm), perforated metal foil (thickness 10 to 100 μm, hole diameter 0.1 to 10 mm), expanded metal, foam metal plate, glassy carbon plate, etc.

[0064] The metal sulfide layer can be produced by applying a composition that can be used as a positive electrode mixture obtained by adding, as necessary, the conductive assistant, the binder, a solvent, and the like to the metal sulfide, onto the carrier that can be used as a positive electrode current collector, and drying the composition.

[0065] The solvent is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include aqueous solvents and organic solvents. Examples of aqueous solvents include water and alcohols (methanol, ethanol, etc.). Examples of the organic solvents include N-methyl-2-pyrrolidone (NMP) and toluene. These solvents can be used alone or in combination of two or more.

[0066] In addition, it is also possible to directly roll-form the metal sulfide into a sheet shape or to form it into a pellet shape by compression molding.

[0067] The thickness of the metal sulfide layer obtained as described above is not particularly limited. As will be described later, a coating layer of metal oxide can be formed to mold it into the positive electrode of a lithium-ion secondary battery. From the viewpoints of easily maintaining the charge-discharge capacity and easily improving the charge-discharge cycle characteristics, 0.010 to 1.00 mm is preferable, and 0.020 to 0.50 mm is more preferable.

[0068] (1-3) Coating layer In the coated metal sulfide layer of the present invention, the coating material constituting the coating layer contains a metal oxide. Although this metal oxide does not itself contribute to charge and discharge, it can improve the charge-discharge cycle characteristics while maintaining the charge-discharge capacity by the above-described metal sulfide layer.

[0069] In the present invention, as the metal element (M 2 ) constituting the metal oxide, titanium and / or aluminum is preferable from the viewpoints of making it difficult to elute into the electrolytic solution by the formed coating layer, easily maintaining the charge-discharge capacity, and easily improving the charge-discharge cycle characteristics. That is, the metal oxide constituting the formed coating layer is preferably a titanium oxide (for example, TiO x1 ; 1 < x1 ≦ 2) and / or an aluminum oxide (for example, Al2O x2 ; 2 < x2 ≦ 3). In particular, titanium oxide and / or aluminum oxide is preferable. These elements can be used alone or in combination of two or more.

[0070] From the viewpoint of enhancing the crystallinity of the coating material constituting the coating layer and further improving the charge-discharge cycle characteristics, a crystalline material is preferable as the coating material constituting such a coating layer.

[0071] The coating layer containing the above-mentioned coating material coats all or part of the surface of the above-mentioned metal sulfide layer. In particular, in order to coat uniformly and further suppress the elution of metal sulfide and further improve charge-discharge cycle characteristics, it is preferable that the entire surface of the metal sulfide layer is coated. From this viewpoint, the coverage of the coating layer is preferably 50 to 100%, more preferably 70 to 100%, and even more preferably 80 to 100%. The coverage of the coating layer is measured by SEM-EDX measurement. In the present invention, the coverage is the ratio of the number of metal elements (M 2 ) indicates the ratio of the number of particles detected to be 0.10 atomic % or more.

[0072] The thickness of the coating layer made of the above-mentioned coating material is preferably 0.010 μm to 0.50 mm, more preferably 0.10 μm to 0.050 mm, from the viewpoints of making the coating layer less susceptible to elution by the electrolyte, facilitating maintenance of charge / discharge capacity, and facilitating improvement of charge / discharge cycle characteristics. The thickness of the coating layer is measured by SEM / EDX method in the cross-sectional direction.

[0073] In addition, in the coated metal sulfide layer of the present invention, since the coated metal sulfide layer is coated with the above-mentioned coating layer, the metal element (M 2 Specifically, in the range of 0.50 to 1.5 μm from the surface of the coated metal sulfide of the present invention, when the element concentration distribution is measured in the cross-sectional direction by the SEM / EDX method, the metal element (M 2 ) is present at 0.5 to 100 atomic % on the outermost surface, and preferably at 1 to 50 atomic %. In addition, in the range of 0.5 to 1.5 μm from the surface of the coated metal sulfide of the present invention, when the element concentration distribution is measured in the cross-sectional direction by SEM / EDX method, the metal elements (M 1 ) is present in an amount of preferably 5 to 30 atomic %, and more preferably 10 to 20 atomic %.

[0074] The coating metal sulfide layer of the present invention may contain other impurities as long as they do not impair the performance. Such impurities include, in addition to the above-mentioned raw materials for the metal sulfide, metal atoms (M 1 ), oxygen that may be mixed into the raw materials or during production, etc.

[0075] The amount of these impurities is preferably within a range that does not impair performance, and is usually preferably 2 mass% or less (0 to 2 mass%), more preferably 1.5 mass% or less (0 to 1.5 mass%). However, as described above, it is preferable that elemental sulfur is not contained as much as possible as an impurity.

[0076] The coating metal sulfide layer of the present invention described above has excellent charge / discharge capacity while also being capable of improving charge / discharge cycle characteristics, and is therefore useful as a positive electrode for a lithium ion secondary battery (particularly a positive electrode for a lithium-sulfur battery).

[0077] 2. Manufacturing method of the coated metal sulfide layer The method for producing the coated metal sulfide layer of the present invention is not particularly limited. For example, (1A) applying a solution of a metal alkoxide to the surface of the metal sulfide layer; or (1B) A step of coating the surface of the metal sulfide layer with the metal oxide by a sputtering method. The method can be produced by a method comprising the steps of:

[0078] In addition, when step (1A) is adopted, thereafter, (2A) Exposure to the atmosphere can also be adopted.

[0079] Furthermore, after step (1A), (1B) or (2A), (3) Heat treatment process It can also be provided with:

[0080] As the metal sulfide layer, those mentioned above can be used.

[0081] (2-1) Wet method (coating) There is no particular limitation on the metal alkoxide used to form the coating layer, so long as it is a material (metal oxide precursor) that can produce a metal oxide by reaction. 2 It is preferable to use a metal alkoxide having the same structure as that of the metal alkoxide (e.g., titanium ethoxide, titanium isopropoxide, etc.). Among them, from the viewpoints of ease of forming a coating layer, solubility in a solvent as a coating layer, etc., titanium alkoxides (e.g., titanium ethoxide, titanium isopropoxide, etc.), aluminum alkoxides (e.g., aluminum isopropoxide, etc.), etc. are preferable. These metal alkoxides can be used alone or in combination of two or more kinds.

[0082] In the metal alkoxide solution, a solvent that can disperse the metal sulfide in the metal sulfide layer without reacting or dissolving and dissolve the above-mentioned metal alkoxide is preferable. Specifically, higher alcohols (especially alcohols having 3 to 6 carbon atoms) such as n-propyl alcohol, isopropyl alcohol, n-butyl alcohol, sec-butyl alcohol, isobutyl alcohol, and tert-butyl alcohol are preferable. This makes it easy to suppress the metal sulfide in the metal sulfide from reacting and dissolving.

[0083] In addition, when the above-mentioned higher alcohol is used as the solvent, it is preferable that it is highly dehydrated. Specifically, the water content is preferably 0.0 to 50 ppm, particularly 0.0 to 10 ppm, based on 100% by mass of the total amount of the higher alcohol. The dehydration method is not particularly limited, and can be carried out by a conventional method. It is preferable that these solvents are appropriately selected depending on the metal sulfide and metal alkoxide in the metal sulfide layer to be used. In addition, these solvents can be used alone or in combination of two or more kinds.

[0084] The concentration of the metal alkoxide in the metal alkoxide solution is not particularly limited, but is preferably adjusted so that the metal sulfide layer can be easily covered and the coverage rate is as described above. Specifically, the concentration is preferably 1 to 15% by volume, and more preferably 2 to 5% by volume, based on 100% by volume of the total amount of the metal alkoxide solution.

[0085] The method of applying the metal alkoxide solution to the surface of the metal sulfide layer is not particularly limited, and may be, for example, screen printing, doctor blade, dip coating, spray coating, spin coating, bar coating, a squeegee method, inkjet printing, or the like.

[0086] This allows a coating layer to be formed on the surface of the metal sulfide layer, and the metal alkoxide can then be exposed to the atmosphere, which allows the moisture in the atmosphere to react with the metal alkoxide, making it easier to form a coating layer of metal oxide on the surface of the metal sulfide layer.

[0087] When the obtained coated metal sulfide layer is exposed to the atmosphere, the exposure time is not particularly limited, but from the viewpoints of making it easier to form a metal oxide coating layer on the surface of the metal sulfide layer, making it easier to maintain the charge / discharge capacity, and making it easier to improve the charge / discharge cycle characteristics, it is preferably 5 to 300 minutes, and more preferably 10 to 240 minutes.

[0088] When the obtained coating metal sulfide layer is exposed to the atmosphere, it is preferable to perform a post-treatment such as drying and / or heat treatment, which is usually performed in the atmosphere. This makes it easier to further improve the charge / discharge cycle characteristics while maintaining the charge / discharge capacity. In this case, the temperature of the drying and / or heat treatment is not particularly limited, but even by heating at a low temperature, the coverage rate can be further improved and a strong and uniform coating layer can be easily formed. On the other hand, in order to easily suppress the decomposition of the metal sulfide due to high-temperature heating, it is preferable to avoid heating at too high a temperature. For this reason, the heating temperature is preferably 25 to 120°C, more preferably 70 to 115°C. In addition, the heating time is preferably 20 to 600 minutes, more preferably 90 to 480 minutes. In addition, it is generally said that elemental sulfur is eluted from the metal sulfide itself used in the positive electrode active material when it is heated at a temperature higher than 100°C. In that case, the charge-discharge cycle characteristics are likely to deteriorate, but since the conductive assistant in the coated positive electrode contains a material with excellent heat conductivity, and the base electrode plate uses a metal foil with excellent heat conductivity, it is possible to suppress the detachment of sulfur to some extent even in an environment exceeding 115 ° C, which is the melting point of sulfur. In the present invention, as described above, after the metal sulfide is synthesized, it is possible to produce a coated metal sulfide layer at a temperature of 120 ° C or less in all steps. In addition, it is not expected that a temperature higher than 120 ° C will be applied to the positive electrode active material during the manufacture of a lithium ion secondary battery or during charging and discharging. Therefore, from this perspective, the present invention makes it easy to suppress the elution of elemental sulfur and improve the charge-discharge cycle characteristics.

[0089] (2-2) Sputtering method (coating) In the coated metal sulfide layer of the present invention, the coating layer can also be formed by a sputtering method. When forming a coating layer on metal sulfide particles, even if the coating layer is formed by a sputtering method, the coverage cannot be increased, and the effect of improving the charge-discharge cycle characteristics is limited. However, when coating a metal sulfide layer, the coating layer can be sufficiently formed by the sputtering method, and the charge-discharge cycle characteristics can be sufficiently improved.

[0090] The atmosphere in which the sputtering method is performed is preferably an inert gas atmosphere such as a nitrogen gas atmosphere or an argon gas atmosphere, since this makes it easy to improve the coverage rate of the metal oxide coating layer and to improve the charge-discharge cycle characteristics while maintaining the charge-discharge capacity.

[0091] The pressure when performing the sputtering method is not particularly limited, but is preferably 0.1 to 100 Pa, and more preferably 1 to 10 Pa, because this makes it easy to improve the coverage by the metal oxide coating layer and to improve the charge-discharge cycle characteristics while maintaining the charge-discharge capacity.

[0092] The voltage when performing the sputtering method is not particularly limited, but is preferably 150 to 450 V, and more preferably 200 to 400 V, because this makes it easy to increase the coverage by the metal oxide coating layer and to improve the charge-discharge cycle characteristics while maintaining the charge-discharge capacity.

[0093] After obtaining the coated metal sulfide layer by the sputtering method, a heat treatment can be performed. This makes it easier to maintain the charge / discharge capacity while further improving the charge / discharge cycle characteristics. At this time, there is no particular limit to the temperature of the heat treatment, but even by heating at a low temperature, it is easier to maintain the charge / discharge capacity while further improving the charge / discharge cycle characteristics. On the other hand, in order to easily suppress the decomposition of the metal sulfide due to high-temperature heating, it is preferable to avoid heating at too high a temperature. For this reason, the heating temperature is preferably 25 to 120°C, more preferably 70 to 115°C. In addition, the heating time is preferably 20 to 600 minutes, more preferably 90 to 480 minutes. In general, it is said that the elemental sulfur is eluted from the metal sulfide used in the positive electrode active material when it is heated at a temperature higher than 100°C, but in the coated positive electrode, the conductive assistant contains a material with excellent heat conductivity, and the base electrode plate uses a metal foil with excellent heat conductivity, so it is possible to suppress the detachment of sulfur to some extent even in an environment exceeding 115°C, which is the melting point of sulfur. In that case, the charge / discharge cycle characteristics are likely to deteriorate. In the present invention, as described above, after the synthesis of the metal sulfide, it is possible to produce a coated metal sulfide layer at a temperature of 120° C. or less in all steps. In addition, it is not expected that the positive electrode active material will be subjected to a temperature higher than 120° C. during the manufacture of a lithium ion secondary battery or during charging and discharging. Therefore, from this perspective, the present invention is easy to suppress the elution of elemental sulfur and easy to improve the charge and discharge cycle characteristics.

[0094] The coating metal sulfide layer thus produced can improve the charge-discharge cycle characteristics while maintaining the charge-discharge capacity.

[0095] 3. Positive electrodes for lithium-ion batteries and lithium-ion secondary batteries The coated metal sulfide layer of the present invention can be effectively used as a positive electrode of a lithium ion secondary battery by utilizing the property of improving the charge / discharge cycle characteristics while maintaining the charge / discharge capacity as described above. In this specification, the lithium ion secondary battery means a secondary battery that charges and discharges using lithium ions as a charge carrier, and includes a metal lithium secondary battery using lithium metal as a negative electrode active material and a lithium-sulfur battery using a sulfur-containing material as a positive electrode active material. In particular, the coated metal sulfide layer of the present invention is useful as a positive electrode for a lithium ion secondary battery (particularly, a positive electrode for a lithium-sulfur battery) since it improves the charge / discharge cycle characteristics while maintaining the charge / discharge capacity of the metal sulfide in the metal sulfide layer. The lithium ion secondary battery using the coated metal sulfide layer of the present invention as a positive electrode has the characteristic of being excellent in charge / discharge cycle characteristics because it is difficult to dissolve in the electrolyte, and is therefore preferably used in a nonaqueous electrolyte lithium ion secondary battery using a nonaqueous solvent-based electrolyte as the electrolyte.

[0096] The structure of the non-aqueous electrolyte lithium ion secondary battery can be the same as that of a known lithium ion secondary battery, except that the coating metal sulfide layer of the present invention is used as the positive electrode. For example, the basic structure can be the same as that of a known non-aqueous electrolyte lithium ion secondary battery, except that the above-mentioned coating metal sulfide layer is used as the positive electrode.

[0097] As the negative electrode active material, for example, lithium metal, carbon-based materials (activated carbon, graphite, etc.), silicon, silicon oxide, Si-SiO-based materials, lithium titanium oxide, and other known negative electrode active materials can be used. From the viewpoint of charge / discharge capacity, lithium metal is preferred. These negative electrode active materials can be supported on a negative electrode current collector made of aluminum, nickel, titanium, gold, silver, copper, stainless steel, carbon, etc., using a conductive assistant, binder, etc., as necessary. As the conductive assistant, for example, carbon materials (graphite, coke, carbon black, activated carbon, etc.), conductive fibers (acicular carbon; carbon nanotubes; vapor-grown carbon, fibers produced by carbonizing pitch (a by-product of petroleum, coal, coal tar, etc.) at high temperatures; carbon fibers produced from acrylic fibers), corrosion-resistant metals (titanium, gold, etc.), carbides (SiC, WC, etc.), nitrides (Si3N4, BN, etc.), etc. can also be used. The binder is not particularly limited and may be a known material, such as styrene-butadiene rubber, carboxymethyl cellulose, polyvinylidene fluoride (PVDF), polyimide, etc. In addition, a binder having a reactive group that crosslinks by heating, ultraviolet irradiation, etc. may be suitably used. Examples of the reactive group include a vinylene group, a hydroxyl group, an epoxy group, an allyl group, a carbonyl group, and a reactive group in which a part of the carbon atom of the reactive group is substituted with a different element. The shape of the negative electrode current collector is also not particularly limited, and may be a metal foil (thickness 10 to 100 μm), a perforated metal foil (thickness 10 to 100 μm, hole diameter 0.1 to 10 mm), an expanded metal, a foamed metal plate, a glassy carbon plate, etc.

[0098] The separator may be made of a material such as a polyolefin resin, such as polyethylene or polypropylene, a fluororesin, nylon, aromatic aramid, or inorganic glass, and may be in the form of a porous film, a nonwoven fabric, or a woven fabric.

[0099] The non-aqueous electrolyte is not particularly limited, and a combination of a known organic solvent and an electrolyte salt can be used. As the solvent for the non-aqueous electrolyte, a known solvent for a non-aqueous solvent-based secondary battery, such as carbonate, ether, nitrile, sulfur-containing compound, ionic liquid, solvated ionic liquid, etc., can be used. In particular, when elemental sulfur is used as the positive electrode active material, if carbonate is used as the solvent, elemental sulfur and carbonate react with each other, and if ether is used as the solvent, the sulfur component dissolves in a large amount in the electrolyte, causing performance deterioration, so these solvents could not be used. However, when the coated metal sulfide layer of the present invention is used as the positive electrode, these problems can be solved, so any solvent can be applied, and the selectivity of the solvent in the non-aqueous electrolyte can be improved.

[0100] The shape of the nonaqueous electrolyte lithium ion battery is not particularly limited, and any shape such as a cylindrical shape or a rectangular shape can be used. EXAMPLES

[0101] The present invention will be specifically described below with reference to examples and comparative examples. However, it goes without saying that the present invention is not limited to only the examples shown below.

[0102] Synthesis Example 1: Synthesis of vanadium sulfide particles Commercially available vanadium(III) sulfide (V2S3; manufactured by Kojundo Chemical Laboratory Co., Ltd.) and sulfur (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were weighed in a glove box (dew point -80°C) in an argon gas atmosphere so that the molar ratio was 1:6, and the mixture was sealed in a glass tube in a vacuum. The vacuum-sealed sample was fired in a tubular furnace at 400°C for 5 hours. The fired sample was fired in a vacuum at 200°C for 8 hours to desulfurize the excess sulfur and synthesize crystalline vanadium sulfide VS4 (c-VS4) particles.

[0103] Next, the obtained crystalline VS4 (c-VS4) particles were subjected to mechanical milling (ball diameter 4 mm, rotation speed 270 rpm) for 40 hours in a glove box (dew point -80°C) in an argon gas atmosphere using a ball mill (Fritsch PL-7) to synthesize low-crystalline vanadium sulfide VS4 (a-VS4) particles. The average particle size of the obtained low-crystalline vanadium sulfide VS4 (a-VS4) was about 3 μm when observed in a scanning electron microscope photograph with a field of view of 13 μm x 9 μm and an average number of 10 or more particles.

[0104] Synthesis Example 2: Synthesis of vanadium sulfide layer The low-crystalline vanadium sulfide VS4 (a-VS4) particles obtained in Synthesis Example 1, a conductive material (Ketjen black), and a binder (polytetrafluoroethylene) were mixed in a mortar so that the ratio of low-crystalline vanadium sulfide VS4 (a-VS4) particles:conductive material:binder was 8:4:1 (mass ratio), and the mixture was attached to an aluminum mesh to produce a vanadium sulfide layer (thickness 45 μm).

[0105] Example 1 A mixed solution was obtained by adding 3.7 mass % of water to 100 mass parts of an isopropyl alcohol solution of titanium isopropoxide Ti[OCH(CH3)2]4 with a concentration of 5 volume %.

[0106] The resulting mixed solution was applied to the vanadium sulfide layer obtained in Synthesis Example 2 in air using an applicator so that the thickness before drying was 70 μm.

[0107] The obtained vanadium sulfide layer was then exposed to the air for 2 hours, and then heat-treated in a vacuum at 80° C. for 2 hours. As a result, a coated vanadium sulfide layer (positive electrode) was obtained in which a titanium oxide coating film having a thickness of 4.3 μm was formed on the surface of the vanadium sulfide layer.

[0108] Example 2 In the air, a 5% by volume solution of titanium isopropoxide Ti[OCH(CH3)2]4 in isopropyl alcohol was applied to the vanadium sulfide layer obtained in Synthesis Example 2 using an applicator to a thickness of 70 μm before drying.

[0109] The obtained vanadium sulfide layer was then exposed to the air for 1 hour, and then heat-treated in a vacuum at 80°C for 2 hours. As a result, a coated vanadium sulfide layer (positive electrode) was obtained in which a titanium oxide coating film having a thickness of 3.4 μm was formed on the surface of the vanadium sulfide layer.

[0110] Example 3 The same treatment as in Example 2 was carried out except that the exposure time in the atmosphere was set to 2 hours, and a coated vanadium sulfide layer (positive electrode) was obtained.

[0111] Example 4 The same treatment as in Example 2 was carried out except that the exposure time in the atmosphere was 3 hours, and a coated vanadium sulfide layer (positive electrode) was obtained.

[0112] Example 5 Under an argon atmosphere, an isopropyl alcohol solution of titanium isopropoxide Ti[OCH(CH3)2]4 having a concentration of 5% by volume was applied to the vanadium sulfide layer obtained in Synthesis Example 2 with an applicator to a thickness of 70 μm before drying.

[0113] The obtained vanadium sulfide layer was then exposed to the air for 2 hours, and then heat-treated in vacuum at 80° C. for 2 hours. As a result, a coated vanadium sulfide layer (positive electrode) was obtained in which a titanium oxide coating film having a thickness of 4.5 μm was formed on the vanadium sulfide layer.

[0114] Example 6 Under an argon atmosphere, an isopropyl alcohol solution of titanium isopropoxide Ti[OCH(CH3)2]4 having a concentration of 5% by volume was applied to the vanadium sulfide layer obtained in Synthesis Example 2 with an applicator to a thickness of 70 μm before drying.

[0115] The obtained vanadium sulfide layer was then dried under an argon atmosphere, and then heat-treated in vacuum at 80° C. for 2 hours. As a result, a coated vanadium sulfide layer (positive electrode) was obtained in which a titanium oxide coating film having a thickness of 6.0 μm was formed on the vanadium sulfide layer.

[0116] Comparative Example 1 The vanadium sulfide layer obtained in Synthesis Example 2 was used as the positive electrode.

[0117] Comparative Example 2 The vanadium sulfide layer obtained in Synthesis Example 2 was exposed to the air for 2 hours, and then heat-treated in vacuum at 80° C. for 2 hours. After heat-treatment at 80° C. for 2 hours, a vanadium sulfide layer (positive electrode) was obtained.

[0118] Test example 1: Cross-section observation The coated vanadium sulfide layer (cathode) obtained in Example 3 and the vanadium sulfide layer obtained in Synthesis Example 2 (the vanadium sulfide layer (cathode) of Comparative Example 1) were observed by cross-sectional scanning electron microscope (cross-sectional SEM) and EDX. The results are shown in FIG. 1. In FIG. 1, the left image is a secondary electron image by cross-sectional SEM, the middle image is an EDX image of titanium, and the right image is an EDX image of oxygen. As a result, the obtained coated vanadium sulfide layers, including those of Examples other than Example 3, were completely covered with a titanium oxide layer (coverage rate 100%), suggesting that titanium is present only in the vicinity of the surface of the coated vanadium sulfide layer and not diffused deep into the coated vanadium sulfide layer. Note that the vanadium sulfide layers of Comparative Examples 1 and 2 were not covered, and therefore the coverage rate was 0%.

[0119] Test Example 2: Elemental Concentration Distribution The element concentration distribution of the coated vanadium sulfide layer (positive electrode) obtained in Example 3 was measured by line analysis using a cross-sectional SEM / EDX. The results are shown in Figure 2. As a result, in the range of 0.50 to 1.5 µm from the surface of the coated vanadium sulfide layer obtained in Example 3, titanium element was present at 2.3 atomic % and vanadium element was present at 15 atomic %.

[0120] Test example 3: Charge / discharge test Using the coated vanadium sulfide layers or vanadium sulfide layers obtained in Examples 1 to 6 and Comparative Examples 1 and 2 as positive electrodes, test electrochemical cells (lithium secondary batteries) were produced by the following method, and constant current charge / discharge measurements were performed at 25°C, a current density of 200 mA / g (charge / discharge rate: 0.20 C), a voltage range of 1.5 to 2.6 V, and a rest time between cycles of 10 minutes.

[0121] The counter electrode (negative electrode) was lithium metal. The electrolyte was 1M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) dissolved in a 1:1 mass ratio mixed solvent of ethylene carbonate (EC) and propylene carbonate (PC) (1M LiTFSI EC / PC). Polypropylene was used as the separator.

[0122] A comparison of the discharge capacities of the coated vanadium sulfide layer or vanadium sulfide layer obtained in Example 3 and Comparative Example 1 in accordance with the charge-discharge cycle is shown in Fig. 3. The capacity maintenance rates in each cycle of Examples 1 to 6 and Comparative Examples 1 to 2 are also shown in Table 1. As can be seen from Comparative Examples 1 and 2, generally, when a metal sulfide is subjected to a heat treatment, both the charge-discharge capacity and the charge-discharge cycle characteristics deteriorate, but as in Examples 1 to 6, by covering the surface of the vanadium sulfide layer with a coating layer of a metal oxide, the charge-discharge cycle characteristics could be improved while maintaining the charge-discharge capacity.

[0123] [Table 1]

[0124] Example 7 The vanadium sulfide layer obtained in Synthesis Example 2 was punched out to prepare a sample for sputtering. Using a sputtering device SC-701MkII Adv. manufactured by Sanyu Electronics Co., Ltd., sputtering was performed for 5 minutes with aluminum as the film type (target), room temperature (25°C) as the treatment temperature, argon gas atmosphere at 8.0 Pa, and treatment voltage of 270 to 300 V (initial applied voltage of 475 V), to form an aluminum oxide coating layer on the surface of the vanadium sulfide layer, thereby obtaining a coated vanadium sulfide layer (positive electrode).

[0125] In addition, under the sputtering conditions in this embodiment, the coverage rate was 100% in all embodiments, and the thickness of the coating layer was almost the same for both titanium and aluminum, as follows: 5 minute sputtering: approximately 0.6 μm, 10 minute sputtering: approximately 0.9 μm, 15 minute sputtering: approximately 1.3 μm, 30 minute sputtering: approximately 2.5 μm.

[0126] Example 8 The same treatment as in Example 7 was carried out except that the sputtering treatment time was 10 minutes, and a coated vanadium sulfide layer (positive electrode) was obtained.

[0127] Example 9 The same treatment as in Example 7 was carried out except that the sputtering treatment time was 15 minutes, and a coated vanadium sulfide layer (positive electrode) was obtained.

[0128] Example 10 The same treatment as in Example 7 was carried out except that the sputtering treatment time was 20 minutes, and a coated vanadium sulfide layer (positive electrode) was obtained.

[0129] Example 11 The same treatment as in Example 7 was carried out except that the sputtering treatment time was 30 minutes, and a coated vanadium sulfide layer (positive electrode) was obtained.

[0130] Example 12 The same treatment as in Example 7 was carried out except that the sputtering treatment time was 45 minutes, and a coated vanadium sulfide layer (positive electrode) was obtained.

[0131] Example 13 The same treatment as in Example 7 was carried out except that the sputtering treatment time was 60 minutes, and a coated vanadium sulfide layer (positive electrode) was obtained.

[0132] Example 14 The same treatment as in Example 7 was carried out except that the film type (target) was titanium, and a coated vanadium sulfide layer (positive electrode) was obtained.

[0133] Example 15 The same treatment as in Example 7 was carried out except that the film type (target) was titanium and the sputtering treatment time was 10 minutes, to obtain a coated vanadium sulfide layer (positive electrode).

[0134] Example 16 The same treatment as in Example 7 was carried out except that the film type (target) was titanium and the sputtering treatment time was 15 minutes, to obtain a coated vanadium sulfide layer (positive electrode).

[0135] Example 17 The same treatment as in Example 7 was carried out except that the film type (target) was titanium and the sputtering treatment time was 30 minutes, to obtain a coated vanadium sulfide layer (positive electrode).

[0136] Example 18 The vanadium sulfide layer obtained in Synthesis Example 2 was punched out to prepare a sample for sputtering. Using a sputtering device SC-701MkII Adv. manufactured by Sanyu Electronics Co., Ltd., sputtering was performed for 15 minutes with aluminum as the film type (target), room temperature (25°C), argon gas atmosphere at 8.0 Pa, and voltage of 270 to 300 V (initial applied voltage of 475 V), followed by heat treatment in vacuum at 80°C for 6 hours to form an aluminum oxide coating layer on the surface of the vanadium sulfide layer, thereby obtaining a coated vanadium sulfide layer (positive electrode).

[0137] Example 19 The same treatment as in Example 18 was carried out except that the film type (target) was titanium, and a coated vanadium sulfide layer (positive electrode) was obtained.

[0138] Test Example 4: Cross-section observation The coated vanadium sulfide layer (cathode) obtained in Example 17 and the vanadium sulfide layer obtained in Synthesis Example 2 (vanadium sulfide layer (cathode) of Comparative Example 1) were observed by cross-sectional scanning electron microscope (cross-sectional SEM) and EDX. The results are shown in FIG. 4. In FIG. 4, the left image is a secondary electron image by cross-sectional SEM, the middle image is an EDX image of aluminum, and the right image is an EDX image of oxygen. As a result, the obtained coated vanadium sulfide layers, including those of Examples other than Example 17, were completely covered with a titanium oxide layer or an aluminum oxide layer (coverage rate is 100%), suggesting that aluminum is present only near the surface of the coated vanadium sulfide layer and has not diffused deep into the coated vanadium sulfide layer.

[0139] Test Example 5: Elemental Concentration Distribution The element concentration distribution of the coated vanadium sulfide layer (positive electrode) obtained in Example 17 was measured by line analysis using a cross-sectional SEM / EDX. The results are shown in Figure 5. As a result, in the range of 0.50 to 1.5 µm from the surface of the coated vanadium sulfide layer obtained in Example 17, titanium element was present at 0.9 atomic % and vanadium element was present at 12 atomic %.

[0140] Test Example 6: Charge / Discharge Test Using the coated vanadium sulfide layers or vanadium sulfide layers obtained in Examples 7 to 19 and Comparative Example 1 as positive electrodes, test electrochemical cells (lithium secondary batteries) were produced by the following method, and constant current charge / discharge measurements were performed at 25°C, a current density of 200 mA / g (charge / discharge rate: 0.20 C), a voltage range of 1.5 to 2.6 V, and a rest time between cycles of 10 minutes.

[0141] The counter electrode (negative electrode) was lithium metal. The electrolyte was 1M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) dissolved in a 1:1 mass ratio mixed solvent of ethylene carbonate (EC) and propylene carbonate (PC) (1M LiTFSI EC / PC). Polypropylene was used as the separator.

[0142] A comparison of the discharge capacities of the coated vanadium sulfide layers or vanadium sulfide layers obtained in Example 17 and Comparative Example 1 in relation to the charge-discharge cycles is shown in Fig. 6. The capacity retention rates in each cycle of Examples 7 to 19 and Comparative Example 1 are shown in Table 2. Even when sputtering was performed as in Examples 7 to 19, the charge-discharge cycle characteristics could be improved while improving the charge-discharge capacity by covering the surface of the vanadium sulfide layer with a metal oxide coating layer.

[0143] [Table 2]

Claims

1. The whole or a part of the metal sulfide layer containing a metal sulfide is coated with a coating layer containing a metal oxide, and The metal sulfide has a composition ratio of sulfur to metal (S / M 1 ) is in a molar ratio of 2.1 to 10, The metal sulfide is vanadium sulfide; the metal oxide is an oxide of titanium and / or aluminum, The coating layer has a coverage of 70 to 100%.

2. The coating metal sulfide layer according to claim 1, wherein the average particle size of the metal sulfide is 1.0 to 20.0 μm.

3. The coating metal sulfide layer according to claim 1 or 2, wherein the thickness of the metal sulfide layer is 0.010 μm to 1.00 mm.

4. A method for producing a coated metal sulfide layer according to any one of claims 1 to 3, (1A) applying a solution of titanium alkoxide and / or aluminum alkoxide to the surface of the metal sulfide layer; or (1B) A step of coating the surface of the metal sulfide layer with the metal oxide by a sputtering method. A manufacturing method comprising:

5. The method according to claim 4, wherein the solvent in the titanium alkoxide and / or aluminum alkoxide solution is an alcohol having 3 to 6 carbon atoms.

6. After the step (1A), (2A) Step of exposing to the atmosphere The method of claim 4 or 5, comprising:

7. After the step (1A), (1B) or (2A), (3) Heat treatment process The method according to any one of claims 4 to 6, comprising:

8. A positive electrode for a lithium ion secondary battery comprising the coating metal sulfide layer according to any one of claims 1 to 3.

9. A lithium ion secondary battery comprising the positive electrode for lithium ion secondary batteries according to claim 8.

Citation Information

Patent Citations

  • Nanorod-like vanadium tetrasulfide powder and preparation method and application thereof

    CN110282660A

  • Negative active material for lithium secondary battery, manufacturing method therefor, and lithium secondary battery

    JP2008130571A

  • Electrode active material of molybdenum sulfide coated with metal oxide for sodium secondary battery and fabrication method thereof

    KR1020140107833A

  • Composite of metal sulfide and metal oxide and process for producing the composite

    WO2009113460A1

  • Lithium-iron-manganese-based composite oxide and lithium-ion secondary cell using same

    WO2015025844A1